Efektivitas Humas dan Wartawan dalam Menyosialisasikan Program Website Layanan Aspirasi Diskominfo Labuhan Batu - Sakti Tambak, Ahmad Budi; Saragih, M. Yoserizal; Abidin, Syahrul (Comit: Communication, Information and Technology Journal, 2024)
Communication is a need that cannot be separated from humans. In the develop of mass communication there was a development regarding mass media when the internet was discover. The aim to achieved through this research is: "to determine the effectiveness of public relations and journalists in socializing the aspiration service website program at Diskominfo Labuhan Batu". The type of research carried out in this research is qualitative research, namely research based on post-positivist philosophy, used to examine the condition of natural objects. The results of this research show that the uses of the Labuhan Batu Diskominfo website had been effective, because people with technological developments now demand that ASN/PNS are media literate. So automatically, previously the website might have been widely used by the private sector, now the government is using the website and social media too. Now people are more concern, especially government public relations, who are increasingly concerned that a website can be more representative or competent of the agency's image. The advantages of using the Labuhan Batu Diskominfo website include: we can better share data or public policy information by the Labuhan Batu Diskominfo, it can be use to image the Labuhan Batuc Diskominfo, the information provided is always up to date or the latest.